Wireless sensor security communication and anti-leak locating technology based on region partition in power mobile inspection - Min XU; Lin PENG; Haiyun HAN; Nige LI; Zhansheng HOU (Dianxin kexue)
In order to solve the problem of low transmission efficiency and security of the grid，ensure the normal operation of power network，reduce network burden and improve the security of system access，a secure communication and private key location technology of wireless sensor based on region partition was designed by using the technology of time synchronization verification. The power transmission network in the vast amount of sensor partition effectively improved the efficiency of power grid data transmission. The risk of leakage of the coordinate mapping table to the grid data information was prevented by the leakage of the private key location technology. Through the private key and the time stamp authentication technology，the security level of the system communication was effectively increased.